Risk Factors for Nonalcoholic Fatty Liver Disease with Different Insulin Resistance in a Nonobese Chinese Population - Xiaojuan Wu; Ying Wang; Yumei Jia; Jia Liu; Guang Wang (Journal of Diabetes Research)
Purposes. The aim of this study is to identify the risk factors of nonobese nonalcoholic fatty liver disease (NAFLD) individuals under different insulin resistance status. Methods. This cross-sectional study was conducted at the Medical Center of Beijing Chaoyang Hospital affiliated with Capital Medical University. NAFLD was diagnosed based upon ultrasonographic findings consistent with fatty liver disease. Results. A total of 1257 nonobese adults (625 non-NAFLD and 632 nonobese NAFLD) with body mass index (BMI) 18.5-24.9 kg/m2 were enrolled in the study. And all patients were divided into homeostasis model assessment of insulin resistance HOMA−IR>1 group and HOMA−IR≤1 group. When all the variables were adjusted in both the HOMA−IR>1 group and HOMA−IR≤1 group, older age (>50 years), higher BMI (23.0-24.9 kg/m2), higher AST (>18 U/L), higher TG (>0.9 mmol/L), higher GLU (>5.25 mmol/L), and higher HbA1C (>5.5%) were associated with higher risks of nonobese NAFLD. In patients with HOMA−IR>1, lower homeostatic model assessment of β-cell function (HOMA-β) (<47.1%) (OR, 7.460, 95% CI, 3.051-18.238, P<0.001) was associated with higher risks of nonobese NAFLD. Conclusions. Metabolic profiles (i.e., higher BMI, hyperglycemia, hypertriglyceridemia, and higher glycosylated hemoglobin) are risk factors of nonobese NAFLD, regardless of insulin resistance status. Decreased function of pancreatic β-cells may be the risk factor of nonobese NAFLD with insulin resistance, who should pay attention to further development of pancreatic β-cell dysfunction.